A trade-off method between environment restoration and human water consumption: A case study in Ebinur Lake. (20th April 2019) - Zeng, Hongwei; Wu, Bingfang; Zhu, Weiwei; Zhang, Ning
Abstract: The shrinkage of inland lakes has become a major problem in arid region. Human activities are competing for water resources with sustainable lake ecosystem. Considering improving irrigation efficiency does not help on water saving at basin scale and reducing ET through mulching, zero tillage and deficit irrigation will lead to crop yield loss, this study proposed an alternative way that returning cropland to lake to achieve the balance between endorheic lake restoration and human water consumption. The approach consists of four procedures: (1) identifying the target annual inflow (Qtar ) of endorheic lake; (2) calculating available consumable water (ACW) in the upstream based on Qtar ; (3) setting ET deduction goals using water consumption balance approach; (4) estimating crop area to be deducted. This approach is implemented at Ebinur Lake of China under two restoration scenarios (lake area restored to 522 km 2 and 800 km 2 ). The results indicate that to restore the Ebinur Lake to 522 km 2, the annual inflow should be increased to 602.6 × 10 6  m³, and human water consumption should be reduced by 320.3 × 10 6  m³. If the restoration goal of Ebinur Lake is set to 800 km 2, an annual inflow of 876.6 × 10 6  m³ is required, and the human water consumption should be reduced by 594.2 × 10 6  m³. The over-expansion of cropland and artificial forest is found to be the main reasons for the shrinkage of Ebinur Lake. Finally, the feasible solutions for ecosystem restoration of Lake Ebinur are provided for both scenarios. The methodology adopted in this research can be applied to the restoration of other inland lakes in arid regions. Highlights: A tradeoff approach is proposed to restore inland lake through reducing ET. It consists of target inflow, available consumable water, ET deduction, and crop area deduction estimation. Over expansion of cropped land is the major reason on the shrinkage of the Ebinur Lake. Reducing cropped land area is a feasible way to restore inland lake in arid regions.